Diagnostic equipment and point-of-care tests in Norwegian emergency primary healthcare clinics: a cross-sectional study - Bent Håkan Lindberg; Jesper Blinkenberg; Tone Morken; Merete Allertsen; Ingrid Keilegavlen Rebnord (Scandinavian Journal of Primary Health Care)
Introduction In recent years, the increasing availability of instruments and laboratory tests has significantly influenced the diagnostic work in primary healthcare. This study aimed to map the availability of diagnostic equipment and point-of-care tests (POCTs) in Norwegian emergency primary healthcare clinics and examine the demographic and organisational factors influencing their availability.Methods This cross-sectional study utilised the National Out-of-Hours Services Registry (NOOHR) survey across all Norwegian emergency primary healthcare clinics in early 2024. Clinic managers provided data on diagnostic equipment and POCTs. Clinics were categorised by population size, hospital proximity, co-location with general practitioner (GP) offices, and total equipment available.Results All 167 Norwegian emergency primary healthcare clinics responded. The median number of diagnostic equipment and POCTs was 17 (Interquartile range (IQR) 16–20). Clinics with the most equipment were often smaller, co-located with a GP office, and over 40 km from a hospital. Almost all clinics had a repertoire of CRP, urinary dipstick, haemoglobin, glucose, strep A test, SARS-CoV-2 rapid test, urinary HCG test, pulse oximeter, and ECG. Clinics far from hospitals more frequently had tests like D-dimer and troponin. Of the clinics with troponin tests, 69% had a low-sensitive POCT.Conclusion Norwegian emergency primary healthcare clinics are well equipped, especially if co-located with a GP office or far from a hospital. Further research is needed to enlighten how availability influences use and the possible impact on patient trajectories. Clinic leaders should pave the way for sustainable practices and high-value care when deciding their diagnostic equipment and POCTs repertoire.